Emotions and Vote Choice : An Analysis of the 2019 Belgian Elections - Close, Caroline; van Haute, Emilie (Politics of the Low Countries, 2025)
This article digs into the relationship between voters’ political resentment and their electoral choice in 2019 by focusing on the respondents’ emotions towards politics. Using the RepResent 2019 voter survey, eight emotions are analysed in their relation to voting behaviour: four negative (anger, bitterness, worry and fear) and four positive (hope, relief, joy and satisfaction). We confirm that voters’ emotional register is at least two-dimensional, with one positive and one negative dimension, opening the possibility for different combinations of emotions towards politics. We also find different emotional patterns across party choices, and more crucially, we uncover a significant effect of emotions (especially negative ones) on vote choice, even when controlling for other determinants. Finally, we look at the effect of election results on emotions and we observe a potential winner vs. loser effect with distinctive dynamics in Flanders and in Wallonia.